Case Report: Abscopal Effect of Microwave Ablation in a Patient With Advanced Squamous NSCLC and Resistance to Immunotherapy - Shao, Chuchu; Yang, Menghang; Pan, Yingying; Xie, Dacheng; Chen, Bin; Ren, Shengxiang; Zhou, Caicun (Frontiers in Immunology, 2021)
Currently, immunotherapy has been a backbone in the treatment of advanced non-small cell lung cancer (NSCLC) without driver gene mutations. However, only a small proportion of NSCLC patients respond to immune checkpoint inhibitors, and majority of patients with initial response will develop acquired resistance at 5 years, which usually manifests as oligo-progression or oligo-metastases. Evidence from multiple clinical trials indicates that local consolidative therapies could improve the prognosis of oligometastatic NSCLC patients. Herein, we reported a case of advanced squamous lung cancer which showed a durable abscopal effect from microwave ablation after acquired resistance of immunotherapy.